Finite element analysis of protective bicycle helmet & dummy head under dynamic loading - Marwan, S. H.; M. Wahi, M. A.; Abdullah, A. H.; Mazlan, M. H. (African Journal Online (AJOL), 2018)
Cycling is a good activities particularly for recreation, exercise, and transportation. However, cycling related to the head injury is a significant contributor to hospitalization and death. Previous literatures indicates that the available helmets have less effective in preventing head injuries among cyclists. Moreover, most of the available helmets have been tested for only a few loading conditions. Therefore, the purpose of this study is to use finite element models to evaluate the protective effect of a helmet against various impact velocities. The head and helmet model has been developed using computational software. This study focus on the explicit dynamic analysis which performed in ANSY-WORKBENCH with loading condition in term of various impact velocity impacted on front and side of the head model. The results indicates the differences between the frontal and side simulations. They have been compared to identify the protective effect of the helmet and head.